The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1152/ajpregu.00169.2005
|View full text |Cite
|
Sign up to set email alerts
|

NMDA channels control meal size via central vagal afferent terminals

Abstract: The N-methyl-D-aspartate (NMDA) ion channel blocker MK-801 administered systemically or as a nanoliter injection into the nucleus of the solitary tract (NTS), increases meal size. Furthermore, we have observed that ablation of the NTS abolishes increased meal size following systemic injection of dizocilpine (MK-801) and that MK-801-induced increases in intake are attenuated in rats pretreated with capsaicin to destroy small, unmyelinated, primary afferent neurons. These findings led us to hypothesize that NMDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…In support of this hypothesis, we have previously reported that administration of NMDA receptor antagonists into the NTS increases food intake (18,23,46). Most interesting, however, is the fact that after degeneration of central vagal afferent terminals, NTS injection of the antagonist does not increase food intake (17). These results are consistent with the working hypothesis that at least some hindbrain NMDA receptors participating in reduction of food intake by vagal signals, including CCK, are located presynaptically on vagal afferent processes in the NTS.…”
Section: Discussionmentioning
confidence: 73%
“…In support of this hypothesis, we have previously reported that administration of NMDA receptor antagonists into the NTS increases food intake (18,23,46). Most interesting, however, is the fact that after degeneration of central vagal afferent terminals, NTS injection of the antagonist does not increase food intake (17). These results are consistent with the working hypothesis that at least some hindbrain NMDA receptors participating in reduction of food intake by vagal signals, including CCK, are located presynaptically on vagal afferent processes in the NTS.…”
Section: Discussionmentioning
confidence: 73%
“…A large series of studies demonstrated a role for glutamate in meal size using localized microinfusions in brain areas associated with feeding or reinforcement (e.g., Zeni et al 2000). Infusions of glutamate in the Nucleus Accumbens decreased food intake, while infusions of glutamate antagonists in the Nucleus Accumbens increased food intake by increasing meal size rodents (Maldonado-Irizarry et al 1995;Stratford et al 1998;Zeni et al 2000), and central infusions of glutamate agonists and antagonists in the pigeon produced a similar pattern of results (Da Silva et al 2006;Gillespie et al 2005). Several studies have also shown that peripheral administration of the NMDA non-competitive antagonist (+)MK-801 (dizocilpine) also increased meal size in the rat (Treece et al 2000;Jahng and Houpt 2001), perhaps due to an increase in the rate of gastric emptying (Covasa et al 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Protons are known to activate the release of bioactive mediators, such as serotonin and cholecystokinin, from the upper small intestine, which activate sensory mechanisms including vagal afferents. 23,24 In fact, several groups have reported increased sensitivity of the duodenum to infused acid. 25,26 However, the precise mechanism for the acid-induced postprandial symptoms is unclear.…”
Section: Discussionmentioning
confidence: 99%